Cerebrotendinous Xanthomatosis: A practice review of pathophysiology, diagnosis, and treatment - Nóbrega, Paulo Ribeiro; Bernardes, Anderson Moura; Ribeiro, Rodrigo Mariano; Vasconcelos, Sophia Costa; Araújo, David Augusto Batista Sá; Gama, Vitor Carneiro de Vasconcelos; Fussiger, Helena; Santos, Carolina de Figueiredo; Dias, Daniel Aguiar; Pessoa, André Luíz Santos; Pinto, Wladimir Bocca Vieira de Rezende; Saute, Jonas Alex Morales; et al. (Frontiers in Neurology, 2022)
Cerebrotendinous Xanthomatosis represents a rare and underdiagnosed inherited neurometabolic disorder due to homozygous or compound heterozygous variants involving the CYP27A1 gene. This bile acid metabolism disorder represents a key potentially treatable neurogenetic condition due to the wide spectrum of neurological presentations in which it most commonly occurs. Cerebellar ataxia, peripheral neuropathy, spastic paraparesis, epilepsy, parkinsonism, cognitive decline, intellectual disability, and neuropsychiatric disturbances represent some of the most common neurological signs observed in this condition. Despite representing key features to increase diagnostic index suspicion, multisystemic involvement does not represent an obligatory feature and can also be under evaluated during diagnostic work-up. Chenodeoxycholic acid represents a well-known successful therapy for this inherited metabolic disease, however its unavailability in several contexts, high costs and common use in patients at late stages of disease course limit more favorable neurological outcomes for most individuals. This review article aims to discuss and highlight the most recent and updated knowledge regarding clinical, pathophysiological, neuroimaging, genetic and therapeutic aspects related to Cerebrotendinous Xanthomatosis.